The relationship between Alexithymia and peer attachment among female students of Hail University - Al-Shammari, Bashayr Nawaf (Journal of Educational and Psychological Sciences, 2025)
This study aimed to identify the relationship between alexithymia and attachment to peers among female students at the University of Hail. The study followed the descriptive, correlational approach, and the study sample consisted of (318) female students, who were selected using a stratified random sampling method. The study tools were the Toronto Alexithymia Scale, Arabi Al Eidan (2019) and the Peer Attachment Scale, Arabi Shehadha and Al-Asmi (2016). The study results showed an average level of alexithymia among the study sample of female students at the University of Hail. There is a high level of peer attachment among the study sample of female students at the University of Hail. A statistically significant inverse correlation exists between alexithymia and peer attachment among female students at the University of Hail. This indicates that the higher the level of exposure of female students at the University of Hail to alexithymia, the lower their level of attachment to peers and vice versa. In light of the results of the study, a set of recommendations was formulated, the most important of which was training female students on how to manage feelings and emotions effectively instead of suppressing them, as they are in dire need of serious and constructive awareness from reliable and purposeful sources to benefit and spread awareness because this age stage is considered the future. Awareness sessions were held on the importance of attachment, its role in daily life, and its dangers. They educated those working with female students on the significance of alexithymia in their relationships and social adjustment with others and prepared guidance programs for female students that address the problem of alexithymia.
Keywords: Alexithymia; Peer Attachment; Female Students at Universityof Hail